Development and function of regulatory innate lymphoid cells - Thomas, Christopher M.; Peebles, R. Stokes (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILCs) are a critical element of the innate immune system and are potent producers of pro-inflammatory cytokines. Recently, however, the production of the anti-inflammatory cytokine IL-10 has been observed in all ILC subtypes (ILC1s, ILC2s, and ILC3s) suggesting their ability to adopt a regulatory phenotype that serves to maintain lung and gut homeostasis. Other studies advocate a potential therapeutic role of these IL-10-expressing ILCs in allergic diseases such as asthma, colitis, and pancreatic islet allograft rejection. Herein, we review IL-10 producing ILCs, discussing their development, function, regulation, and immunotherapeutic potential through suppressing harmful inflammatory responses. Furthermore, we address inconsistencies in the literature regarding these regulatory IL-10 producing ILCs, as well as directions for future research.